Unconscious goal pursuit primes attitudes towards technology usage: A virtual reality experiment. (November 2016) - Triberti, Stefano; Villani, Daniela; Riva, Giuseppe
Abstract: Several approaches in technology adoption, such as the Technology Acceptance Model (TAM), ask future users to provide evaluations of technology. Such evaluations are expected to predict actual use behavior. For example, users' evaluations in terms of perceived usefulness and perceived ease of use are considered meaningful indicators of intention to use the technology, and future usage. However, these approaches still show limited reliability and do not consider other critical aspects, such as situated, unconscious goals and the tendency to perceive related affordances. In order to test the hypothesis that technology evaluation may be influenced by unconscious goals, forty participants were split in two groups. The experimental session included two phases. In the first phase, each group explored a virtual environment that primed a specific goal. In the second phase, participants were asked to evaluate the usefulness and the easiness of use of two versions of the same technology (a mobile devices interface). Results showed that each group evaluated as more useful the version of the technology which featured an affordance related to the respective primed goal. Discussion deals with the possible unconscious influences on attitudes towards technology adoption, and provides operative guidelines to account for them in technology adoption research. Highlights: To investigate the influence of users' goals on evaluation of technology. Virtual Reality is used to prime two different goals in two groups of participants. Technology affording the attainment of the primed goal is perceived as more useful. Perceived easiness of use is not affected by the primed goals.